(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Hypertension is a condition where there is a persistent increase in blood pressure at systolic and diastolic pressure. Hypertension is suffered by Lanisa which can affect her quality of life. The research objective was to determine the effect of social support and physical activity on quality of life. Social support is an individual’s way of interpreting the availability of sources of support that play a role in reducing or suppressing stress symptoms and events. Physical activity is body movement produced by skeletal muscles that requires energy expenditure. Quality of life is a state of how individuals respond physically and emotionally psychologically, socially, work and physically. This type of research is correlational research. The population is elderly people with hypertension in the Nyomplong Village, Working Area of ​​the Pabuaran Health Center, Sukabumi City with a sample of 214 respondents. The sampling technique uses proportional random sampling. Bivariate analysis using Chi square. The results of the hypothesis test showed that there was a relationship between social support and quality of life (p=0.000), there was a relationship between physical activity and quality of life (p=0.000). The conclusion shows that there is a relationship between social support and physical activity on the quality of life of elderly people with hypertension